2019
DOI: 10.1371/journal.pone.0223869
|View full text |Cite
|
Sign up to set email alerts
|

Health workers’ perception of malaria rapid diagnostic test and factors influencing compliance with test results in Ebonyi state, Nigeria

Abstract: BackgroundThe standard practice in treating uncomplicated malaria is to prescribe artemisinin-based combination therapy (ACT) for only patients with positive test results. However, health workers (HWs) sometimes prescribe ACTs for patients with negative malaria rapid diagnostic test (mRDT) results. Available evidence on HWs perception of mRDT and their level of compliance with test results in Nigeria lacks adequate stratification by state and context. We assessed HWs perception of mRDT and factors influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
8
2
Order By: Relevance
“…There was no significant association of respondents' characteristics to their prescribing ACT for negative RDT test results. This contrast a study by Izuchukwu Frank Obi et al [17], which reported prescriber's professional cadre, perception of RDT, training on other causes of fever and health facility level to be significantly associated with ACT prescription to patients with negative RDT results. Prescription of ACTs to negative results may be due to lack of trust for a negative confirmatory result for malaria diagnosis as truly ruling out malaria, poor perception of confirmatory test to detect plasmodium parasite [17], to please patient or not to be seen as incompetent [19].…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…There was no significant association of respondents' characteristics to their prescribing ACT for negative RDT test results. This contrast a study by Izuchukwu Frank Obi et al [17], which reported prescriber's professional cadre, perception of RDT, training on other causes of fever and health facility level to be significantly associated with ACT prescription to patients with negative RDT results. Prescription of ACTs to negative results may be due to lack of trust for a negative confirmatory result for malaria diagnosis as truly ruling out malaria, poor perception of confirmatory test to detect plasmodium parasite [17], to please patient or not to be seen as incompetent [19].…”
Section: Discussioncontrasting
confidence: 81%
“…A holistic training on WHO (testing, treating and tracking) malaria case management will help community pharmacist better appreciate the importance of practicing the WHO T3. Similarly, in a study by Izuchukwu Frank Obi et al [17] amongst health workers in Ebonyi state revealed that respondents socio-demographic characteristics did not impact significantly on health workers practice of malaria diagnosis. However, in this study it was discovered that significantly higher proportion of those who had received Training in testing practiced all three components (Testing, Treatment, and Tracking) of the WHO T3 initiative on malaria case management.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although the National Guidelines for Diagnosis and Treatment of Malaria 2015 4 emphasize the need for parasitological confirmation before prescribing antimalarial drugs, many health care providers (23%–51%) in the public sector prescribe ACTs to clients who test negative for malaria. 5 , 6 The 2018 Nigeria Demographic and Health Survey also found that of 7,466 children younger than 5 years with fever in the 2 weeks preceding the survey, only 1,030 had blood drawn for malaria testing, yet 3,244 children took antimalarials (and over half of those children took ACTs). 7 This suggests that testing and treating based on test results is not widespread.…”
Section: Introductionmentioning
confidence: 99%